Si mulier vinum bibit condemnatur - Zabłocki, Jan (Prawo Kanoniczne, 1989)
Gellius (Gell 10.23..1—2), reffering to the victus and mores of the early Roman women, tells us that the drinking of wine (temetum) was forbidden to women. They were only allowed to drink the lorea, passum, murrina, and other sweet-tasting drinks of that kind. If women drank wine could be punished with the same severity as dultery (Dion. 2.25.6; Gell. 10.23.3). Cato, cited by Gellius (Gell. 10.23.5), has stated that the hasband has right to kill his wife taken in adultery. As regards repudation, says he, in the oration entitled On the Dowry (Gell. 10.23.4), thait iudex has the function of censor. If woman has been guilty of any wrong or shameful act, she is punished (multitatur), (if she has drunk wine or if she has done wrong with another man, she is condemned (condemnatur).